Improving Early Reading Skills through Picture Word Cards at RA Ma'arif III Tanjungarum - Jannah, Khafidatul; Artiningsih, Hindun (Jurnal Profesi Guru Indonesia, 2025)
This study aims to improve early reading skills through picture word cards in Group B children of RA Ma'arif III Tanjungarum - Sukorejo - Pasuruan in the 2024/2025 Academic Year. This is due to the low ability of children to read. This study is a collaborative Class Action using the research model from Kemmis and Mc Taggart which was carried out in two cycles. The subjects of the study were 20 children of Group B consisting of 8 boys and 12 girls. The object of the study was reading ability. Data collection techniques in this study were observation and documentation. The research instrument used was an observation sheet instrument in the form of a checklist, the indicators studied were indicators of the ability to mention letter sound symbols, indicators of mentioning the same phonemes, and indicators of reading words. The data analysis technique was carried out through quantitative descriptive. The indicator of success in this study is if the percentage of each indicator of early reading ability in children has reached ≥80% with good criteria. The results of the study showed that picture word cards can improve reading skills. In the Pre-action stage, the average percentage of children's achievement only reached 42.59%, in the implementation of Cycle I the percentage achieved was 68.34%, and the achievement of early reading skills in Cycle II was 95.57%. The increase from Pre-action to Cycle I was 25.75%, and the increase from Cycle I to Cycle II was 27.23%. The steps for using picture word card media that can improve reading skills are as follows: 1) each group gets 21 picture word card media; 2) the teacher introduces one by one the letter sound symbols that form words; 3) introduces words or nouns that have the same phonemes; 4) reads the word in the picture; and 5) children are guided to match the word card with the appropriate picture, then mention the letter sound symbols, mention the same phonemes, and read the word.